On the Effect of TSN Forwarding Mechanisms on Best-Effort Traffic - Maile, Lisa; Voitlein, Dominik; Arestova, Anna; Hielscher, Kai-Steffen; German, Reinhard (ICCCM '24: Proceedings of the 2024 12th International Conference on Computer and Communications Management, 2024)
Time-Sensitive Networking (TSN) enables the transmission of multiple traffic types within a single network. While the performance of high-priority traffic has been extensively studied in recent years, the performance of low-priority traffic varies significantly between different TSN forwarding algorithms. This paper provides an overview of existing TSN forwarding algorithms and discusses their impact on best-effort traffic. The effects are quantified through simulations of synthetic and realistic networks. The considered forwarding mechanisms are Strict Priority (SP), Asynchronous Traffic Shaper (ATS), Credit-Based Shaper (CBS), Enhanced Transmission Selection (ETS), and Time-Aware Shaper (TAS). The findings indicate that ATS, CBS, and ETS can significantly reduce queuing delays and queue lengths for best-effort traffic when compared to SP and TAS. This effect is enhanced when the reserved bandwidth for high priority queues - using CBS, ATS, or ETS - is reduced to the lowest possible value, within the reserved rate and latency requirements. Specifically, the simulations demonstrate that the choice of forwarding algorithm can improve the performance of low-priority traffic by up to twenty times compared to the least effective algorithm. This study not only provides a comprehensive understanding of the various TSN forwarding algorithms but can also serve as guidance at networks’ design time to improve the performance for all types of traffic.
Keywords: Time-Sensitive Networking; Low-Priority; Scheduling; Forwarding Algorithms; Simulation